ANALISIS KEJADIAN DEPRESI PADA IMIGRAN PENGUNGSI DI WISMA TASQYA PEKANBARU - Alini Alini; Langen Nidhana Meisyalla (Universitas Pahlawan, 2021)
Social conflict can make a group of affected people choose to leave the country and move to another country to gain a sense of security. Pekanbaru is one of the areas in Indonesia which is a temporary shelter for immigrant refugees. Common psychological problems experienced by refugee immigrants include stress and loss of interest as a result of staying in a shelter for too long. This study aims to analyze the incidence of depression in refugee immigrants in Pekanbaru City. This study uses a qualitative approach supported by quantitative data. The population in this study were all registered immigrants living in Tasqya House under the supervision of the Immigration Detention Center (Rudenim) and Kesbangpol Pekanbaru, totaling 136 people. This study used a purposive sampling procedure for selecting respondents. Data collection tools used the Beck Depression Inventory II (BDI II) and interview guides. Analysis of interview data using Collaizi analysis. In this study only 6 (six) subjects were taken for case studies based on the availability of respondents who matched the required characteristics. In the results of the study, it was found that most of the participants experienced moderate depression. The results of this study are expected to provide input to the government to take action on psychological problems experienced by immigrants.